The role of Lyn kinase in the development of imatinib resistance in chronic myelogenous leukemia - Camillo Porta; Federica Tagliani (Frontiers Media S.A., 2011)
Imatinib mesylate, a small-molecule inhibitor of BCRABL tyrosine kinase activity, has emerged as the well-recognized standard of treatment for chronic myelogenous leukemia (CML). Indeed, both its efficacy, tolerability, as well as cost-effectiveness have been clearly proven...